XH-14, a novel danshen methoxybenzo[b]furan derivative, exhibits anti-inflammatory properties in lipopolysaccharide-treated RAW 264.7 cells - Park Geun-Mook; Jun Jong-Gab; Kim Jin-Kyung (BMC, 2013)
Abstract Background XH-14 isolated from Salvia miltiorrhiza is a bioactive component and adenosine antagonist. In the present study, we evaluated anti-inflammatory properties of XH-14 in murine macrophages. Methods RAW 264.7 murine macrophage cell line was cultured with various concentrations of XH-14 in the absence or presence of lipopolysaccharide (LPS). LPS-induced release and mRNA expression of inflammatory mediators were examined by ELISA and real-time PCR. The modification of signal pathways involved in inflammatory reactions was determined by Western blotting analysis. Results XH-14 suppressed the generation of nitric oxide (NO) and prostaglandin E2, and the expression of inducible NO synthase and cyclooxygenase-2 induced by LPS. Similarly, XH-14 inhibited the release of pro-inflammatory cytokines induced by LPS in RAW 264.7 cells. The underlying mechanism of XH-14 on anti-inflammatory action was correlated with down-regulation of mitogen-activated protein kinase and activator protein-1 activation. Conclusions XH-14 inhibits the production of several inflammatory mediators and so might be useful for the treatment of various inflammatory diseases.